A Self‐Assembly Process for the Immobilization of N‐Modified Au Nanoparticles in Ordered Mesoporous Carbon with Large Pores. Issue 16 (6th June 2019) - Li, Hui; Shen, Hong; Pei, Chun; Chen, Shangjun; Wan, Ying
Abstract: A self‐assembly approach has been developed for the immobilization of nitrogen‐modified gold nanoparticles in an ordered mesoporous carbon matrix with large pores. Self‐assembly of the polystyrene‐block‐poly(4‐vinylpyridine) (PS‐ b ‐P4VP) diblock copolymer template coordinated with gold ions and a low‐polymerized phenolic resin leads to a face‐centered cubic mesostructure with F 3 - mm symmetry. Characterization with X‐ray photoelectron spectroscopy and transmission electron microscopy shows that after pyrolysis at 600 °C, monodispersed N‐modified gold nanoparticles approximately 4 nm in size are encapsulated in the ordered mesoporous carbon matrix with open and large pores. The aggregation of Au nanocatalysts into large particles is inhibited due to the coordination between gold and pyridine. The pore size can be tuned from 6 to 12 nm by changing the molecular weight of the PS block. The N‐modified gold catalyst is active in converting benzyl alcohol to benzoic acid using O2 as a green oxidant. Abstract : Get your gold here : Aggregation‐free N‐modified Au nanoparticles (approximately 4 nm) were immobilized in an ordered mesoporous carbon matrix with open and large pores (12 nm) using a self‐assembly approach.